Novel zinc alginate hydrogels prepared by internal setting method with intrinsic antibacterial activity. (10th July 2015) - Straccia, Maria Cristina; d'Ayala, Giovanna Gomez; Romano, Ida; Laurienzo, Paola
Highlights: Zinc alginate hydrogels were prepared via internal gelation for the first time. Zinc alginates show swelling degrees higher than corresponding calcium alginates. Zinc hydrogels show increasing antibacterial activity at increased Zn content. Zinc alginate hydrogels stabilized by calcium preserve antibacterial activity. Zinc alginates stabilized by calcium are stable for prolonged time. Abstract: In this paper, a controlled gelation of alginate was performed for the first time using ZnCO3 and GDL. Uniform and transparent gels were obtained and investigated as potential wound dressings. Homogeneity, water content, swelling capability, water evaporation rate, stability in normal saline solution, mechanical properties and antibacterial activity were assessed as a function of zinc concentration. Gelation rate increased at increasing zinc content, while a decrease in water uptake and an improvement of stability were found. Release of zinc in physiological environments showed that concentration of zinc released in solution lies below the cytotoxicity level. Hydrogels showed antimicrobial activity against Escherichia coli . The hydrogel with highest zinc content was stabilized with calcium by immersion in a calcium chloride solution. The resulting hydrogel preserved homogeneity and antibacterial activity. Furthermore, it showed even an improvement of stability and mechanical properties, which makes it suitable as long-lasting wound dressing.